2020
DOI: 10.3102/0013189x20909822
|View full text |Cite
|
Sign up to set email alerts
|

A Researcher–Practitioner Agenda for Studying and Supporting Youth Reentering School After Involvement in the Juvenile Justice System

Abstract: Across the United States, the rapid spread of “zero-tolerance” policies has generated a pipeline of youth from schools into prisons. Once youth reenter their community and home school, they often struggle to reintegrate. There is relatively little research about school reentry for juvenile justice–involved youth, and yet these students are at risk of low academic achievement, dropping out of school, and recidivism. We propose a conceptual framework for understanding the school reentry process, and then we use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…To make our case, we first review research exploring the school-to-prison pipeline or STPP. We highlight calls to critically historicize the STPP (Meiners, 2007;Rios, 2017;Sojoyner, 2016;Winn & Behizadeh, 2011) and describe what some call a crucial gap in understanding-limited knowledge of students' attempts to reenroll in school after detention (Kubek et al, 2020;Mears & Travis, 2004;Morrison, 2020;Snodgrass Rangel et al, 2020). We draw on Social Justice Youth Development Theory (SJYDT) for its attention to young people's and educators' agency to resist the hardening school/prison nexus, including via YPAR.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…To make our case, we first review research exploring the school-to-prison pipeline or STPP. We highlight calls to critically historicize the STPP (Meiners, 2007;Rios, 2017;Sojoyner, 2016;Winn & Behizadeh, 2011) and describe what some call a crucial gap in understanding-limited knowledge of students' attempts to reenroll in school after detention (Kubek et al, 2020;Mears & Travis, 2004;Morrison, 2020;Snodgrass Rangel et al, 2020). We draw on Social Justice Youth Development Theory (SJYDT) for its attention to young people's and educators' agency to resist the hardening school/prison nexus, including via YPAR.…”
Section: Overviewmentioning
confidence: 99%
“…Others studying the STPP (Cusick et al, 2009;Kubek et al, 2020;Mears & Travis, 2004;Morrison, 2020;Snodgrass Rangel et al, 2020) note a major gap in the field: The need to better understand what could be considered the "other end" or "other direction" of STPPs-what happens when formerly detained students attempt to return to school. As Mears and Travis (2004) write, this gap constitutes a "critical justice policy issue":…”
Section: Critical Gaps: Prison-to-school and Student Voicesmentioning
confidence: 99%
See 1 more Smart Citation
“…This review identified the need to develop a positive identity as one of the top assets that help adolescents reintegrate back to the community. This converges with recent calls to increase researchers-practitioners partnership in addressing the complex intra-and interpersonal challenges faced by youth returning from the juvenile justice system (Snodgrass Rangel et al, 2020).…”
Section: Discussionmentioning
confidence: 72%
“…In light of this situation, the evidence shows what Anderson [ 57 ] calls a “vicious circle of discipline”; that is, the relationship between disciplinary consequences, such as expulsions and suspensions, and academic results, because putting offenders in the juvenile criminal justice system for maintenance of violent behavior [ 58 ] can lead to their dropping out of school [ 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%